Islamic Religious Education in Indonesian Society - Saifuddin; Eni Fariyatul Fahyuni (Adabiyah: Jurnal Pendidikan Islam, 2022)
Education in Islam is very important for human life. There are so many arguments in the Qur'an and hadith that explain the concept of education. Education is important and urgent because the current condition of society is only concerned with knowledge but must pay attention to moral development, morals, and behavior. That's all there is Islamic religious education. This study aims to find out about the implementation of Islamic education in the wider community. The sociological approach in understanding Islam is very important because there are so many religious teachings related to social problems. The research method used is library research. All data obtained and collected are then analyzed and presented from various journal articles that complement the data to provide conclusions. Then reviewed and presented the findings of the data objectively. This study indicates that Islamic religious education is needed by everyone first in social life in Indonesia, which in fact, there are many groups or ethnic groups in Indonesia. The study results show that Islamic religious education is very important in social life in Indonesia because Islamic religious education can make people behave well and follow the rules that exist in Islam.